Agricultura urbana e o enfoque da segurança alimentar e nutricional e soberania alimentar: olhares sobre trajetórias e iniciativas em Varginha-MG - Reis, Thayrine Silva (2020)
The nourishment process has been experimenting transformations of different types: historical, cultural and social ones. Thus, several challenges are being posed to the world population in terms of food and nutrition security and food sovereignty. Amidst those challenges, there is the soaring urbanization of areas towards the more suburban regions and even towards the rural ones. Furthermore, the rural population is increasingly less representative when compared to the urban population figures. Therefore, the urban spaces expand, absorb former rural areas and do not distribute uniformly over its area either the markets or services. Facing a not-so-promising world scenario, the urban and periurban agriculture can, at least at the micro-level, to offer a possibility of improvements in, or even to guarantee, the food and nutrition security, warranting at the same time the food sovereignty. In the case of this work, we have studied a sample of the urban farmers of Varginha-MG. The objective was the analysis of urban and periurban agriculture initiatives in Varginha-MG, from its contributions to nutritional and food security and to food sovereignty. Among the main results, there are findings of this study that this activity has been contributing to improvements in the community's food quantities and quality. Also are important results of this work the psychological and social benefits that are brought about by the activity. However, this undertaking has plenty of challenges. There is no meaningful support from the local government and, sometimes, not even from the population: the access to sources of water is not a simple one, and issues like vandalism, stealing and untrustworthiness are not that uncommon. This work carried out a qualitative analysis of this experience through the extraction of categories that allows its activity to be understood taking into consideration the local context.